Secondary Generalized Cutaneous Mucinosis Developed During Etanercept Treatment in a Patient with Psoriasis - Zhou X; Mubanga D; Chen Z; Bi X (Dove Medical Press, 2022)
Xin Zhou,1,* David Mubanga,2,* Zhuo Chen,3,* Xinling Bi1 1Department of Dermatology, Changhai Hospital, Naval Medical University, Shanghai, 200433, People's Republic of China; 2Department of Dermatology, Maina Soko Military Hospital, Lusaka, Zambia; 3Department of Dermatology, Shanghai Children's Medical Center, Shanghai Jiao Tong University School of Medicine, Shanghai, 200127, People's Republic of China*These authors contributed equally to this workCorrespondence: Xinling Bi, Department of Dermatology, Changhai Hospital, Naval Medical University, Shanghai, 200433, People's Republic of China, Tel +86 13386278946, Email bixinling@163.comAbstract: Cutaneous mucinosis is a rare disease that manifests as an excessive accumulation of mucin in the skin that forms waxy papules or plaques. We report a case of a 44-year-old male psoriatic patient who developed generalized cutaneous mucinosis after 11 months of biological treatment. The patient had a history of psoriasis for 20 years and had been treated with narrow-band UVB phototherapy, methotrexate, or acitretin intermittently. He was started on etanercept after he was diagnosed with psoriatic arthritis, and 11 months later, he complained of swelling in his extremities and myxoid cysts on his fingers. Etanercept was then discontinued due to loss of efficacy and widespread skin lesions. However, the lesions subsided spontaneously after 6 months without specific systemic treatment.Keywords: etanercept, cutaneous mucinosis, psoriasis, biological therapy